Discourse on Human Genetics Research in Mass Media News - Stefanus Khrismasagung Trikusumaadi; Noviana Dewi; Endang Widhiyastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The development of genetic research in humans provides new hope for a better quality of life. One of the studies can reveal the molecular mechanism of a disease, the direction of prevention, and its treatment. Online and offline newspapers are one alternative publication for a wider audience. The purpose of this research is to see how the results of genetic research in humans are constructed in media discourse, both in the form of news, features, and news articles. The ideological content will be explored through an analysis of rhetorical elements in news discourse. This research is a qualitative content analysis, using the discourse analysis method. The unit of analysis is news texts about human genetic research published in 5 online newspapers with the highest readers in the period January - December 2024. Reduction was carried out to obtain relevant news samples. The research results show that the results of human genetic research are discussed in health and lifestyle themes with informative and advocative purposes. The news conveys the latest research results, while also providing recommendations for healthy living at the individual level without a complete explanation in a broader social context. Based on the analysis of rhetorical elements, such presentation indicates the existence of a certain ideology at play in the construction of discourse.